Assessment of carcinogenic PAHs, their oxy-derivatives and heavy metals in soil and sediments from coal mine in Witbank, Mpumalanga Province, South Africa - Nqaba, Zoleka (Vaal University of Technology, 2022)
Fossil fuels provide more than two-thirds of the world’s energy needs with a significant contribution from coal. Coal is referred to as “dirty energy” and it is still used as an energy source because of its vast availability and relatively low cost of production. In South Africa, Witbank mines in Mpumalanga province have the largest coal deposits, supplying power stations that generates 41% of the country’s electricity. Coal mining results in anthropogenic hazardous emissions such as slag waste and coal dust with high concentrations of organic and inorganic pollutants. Polycyclic Aromatic Hydrocarbons (PAHs) are emitted by incomplete coal combustion resulting into coal ash which can contain large quantities of heavy metals. PAHs and heavy metals are known to be major contributors to the environmental pollution due to their negative effects on human health and the ecosystem. As a result this study aims to investigate heavy metals, PAHs and their oxy-derivatives in areas affected by coal soil pollution in Mpumalanga. In this research, 132 soil and sediments samples were collected from 6 coal-containing areas in Mpumalanga (i.e. Greenside coal mine, Kriel power station, Klipfontein dam, Kriel dam, Middleburg dam, and Witbank dam) and these were investigated for their physiochemical properties (pH, TOC, TOM determined by pH electrochemical method and Walkerly Black Method), presence of heavy metals and organics (PAHs and oxy-PAHs). Soil and sediment samples were collected in both winter and summer seasons in 2019. Soil samples were characterised using FTIR and SEM-EDX spectroscopy for functional groups and determination of metal elements, respectively. Heavy metals present in the samples were investigated and the assessment of possible risks of exposure was studied. Heavy metals investigated included Zn, Cu, Co, Fe, Mn, Cr, and Pb. The coefficients of determination of the calibration standards for heavy metals were greater than 0.995 and the recovery values ranged between 75 - 105 %. For the organic pollutants, an extraction method was developed. Organic Pollutants analysed include naphthalene, acenapthene, fluorene, anthracene, pyrene, benzo(a)pyrene and 1,4-naphthalene. Samples were extracted using soxhlet and ultrasonic bath techniques and extracts were analysed using gas chromatography mass spectrometry (GC-MS). The GC-MS method developed was validated by inter-day and intra-day reproducibility of standards, recovery test, linearity of calibration method and limits of quantification and detection. Coefficient determination of the calibration standards were greater than 0.995 for PAHs and recovery values ranged between 60 - 86 %. All the heavy metals that were analysed were detected in all the samples. Generally, it was observed that Greenside and Kriel samples had higher metal concentration as compared to the dams (Klipfontein, Kriel, Middleburg and Witbank) and these had the following range: Fe > Mn > Cr > Pb > Cu > Co. The results for the organics followed a similar trend as the heavy metals, that is, samples from Greenside and Kriel had higher concentration of PAHs as compared to the samples from the dams (Flt > Pyr > Anthr> 1,4-napth > Nap > Flu> benzo(a)anthr > Acy). Based on the results, the concentrations of heavy metals and organics in soil were slightly higher than the World Health Organization limits for these pollutants. This is concerning because the studied areas include residential and agricultural communities. As a result, a continuous and routine monitoring of these pollutants is required to preserve the environment and the health of humans and animals living around the area.
M. Tech. (Department of Biotechnology and Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Heavy metals; Slag waste; Coal dust; Organic and inorganic pollutants.; Polycyclic Aromatic Hydrocarbons (PAHs); Environmental pollution; Dissertations, Academic -- South Africa.; Combined combustion of coal and gas.; Pollution.; Pollutants.; Environmental toxicology.